O-41 Firefighting and cancer: a meta-analysis of cohort studies in the context of cancer hazard identification. (14th March 2023) - DeBono, Nathan; DeBono, Nathan L; Daniels, Robert D; Beane Freeman, Laura E; Graber, Judith M; Hansen, Johnni; Teras, Lauren R; Driscoll, Tim; Kjaerheim, Kristina; Demers, Paul; Glass, Deborah C; Kriebel, David; et al.
Abstract : Objective: We performed a meta-analysis of epidemiological results for the association between occupational exposure as a firefighter and the occurrence of cancer as part of the broader evidence synthesis work of the IARC Monographs Programme. Methods: A systematic literature search was conducted to identify cohort studies of firefighters followed for cancer incidence and mortality. Studies were rated for the influence of key biases on results. Random-effects meta-analysis models were used to estimate the association between ever and duration of employment as a firefighter and risk of 12 selected cancers. The influence of potential biases was explored in sensitivity analyses, including those related to the use of general, uniformed service, and working population comparison groups. Result: Among the 16 cancer incidence studies that met inclusion criteria for one or more cancer sites, the estimated meta-rate ratio, 95% confidence interval (CI), and heterogeneity statistic (I2) for ever-employment as a predominantly male career firefighter compared mostly to general populations was 1.58 (1.14–2.20, 8%) for mesothelioma, 1.16 (1.08–1.26, 0%) for bladder cancer, 1.21 (1.12–1.32, 81%) for prostate cancer, 1.37 (1.03–1.82, 56%) for testicular cancer, 1.19 (1.07–1.32, 37%) for colon cancer, 1.36 (1.15–1.62, 83%) for melanoma, 1.12 (1.01–1.25, 0%) for non-Hodgkin lymphoma, 1.28 (1.02–1.61, 40%) for thyroid cancer, and 1.09 (0.92–1.29, 55%) for kidney cancer. Ever-employment as a firefighter was not positively associated with lung, nervous system, or stomach cancer. Few cancer sites showed increasing risks by employment duration. Results for mesothelioma and bladder cancer exhibited low heterogeneity and were largely robust across sensitivity analyses evaluating bias. Conclusions: There is epidemiological evidence to support a causal role for occupational exposure as a firefighter and certain cancers, especially mesothelioma and bladder cancer. Challenges persist in the body of evidence related to the consistency and quality of exposure assessment and control of confounding and medical surveillance bias.